Alcohol Withdrawal Presenting with Cut Throat Injury during COVID-19 Lockdown: Case Reports from Nepal - Bhattarai, Dipesh; Upadhyaya, Shreeram; Banstola, Hemanta; Pant, Sagun Ballav (Case Reports in Psychiatry, 2023)
Background. The relationship between alcohol dependence and suicidal tendency is well recognized. Self-harm by cut throat is an uncommon but is potentially life-threatening when attempted. We present a description and discussion of a series of three cases of alcohol dependence syndrome who presented with self-inflicted cut throat wounds during the lockdown period from 24th March to 7th July 2020 due to the COVID-19 pandemic at the largest tertiary care hospital in Nepal. Case description. During the three and a half months of COVID-19 lockdown, we had three cases of alcohol dependence syndrome presenting to emergency services with a self-inflicted cut throat injury. Two cases were diagnosed as having alcohol withdrawal delirium and one case as alcohol-induced psychotic disorder (alcoholic hallucinosis) as per the international classification of mental and behavioral disorders diagnostic criteria for research. All three cases were alcohol dependent for more than a decade, but with no prior self-harm attempts. Necessary surgical interventions were done by the Department of Otorhinolaryngology, and in liaison with the Department of Psychiatry, appropriate psychiatric management was done. All three cases had uneventful outcomes in regard to wound care and mental disorder. Conclusion. Suicidal precautions should be taken in alcohol dependence during phases of consumption and abstinence. Screening for alcohol dependence and withdrawal should be a standard process in all self-harm cases that present to the emergency department during a crisis.